Next-generation sequencing applied to rare diseases genomics. (May 2014) - Danielsson, Krissi; Mun, Liew Jun; Lordemann, Amanda; Mao, Jimmy; Lin, Cheng-Ho Jimmy
<x xml:space="preserve">Abstract</x> Genomics has revolutionized the study of rare diseases. In this review, we overview the latest technological development, rare disease discoveries, implementation obstacles and bioethical challenges. First, we discuss the technology of genome and exome sequencing, including the different next-generation platforms and exome enrichment technologies. Second, we survey the pioneering centers and discoveries for rare diseases, including few of the research institutions that have contributed to the field, as well as an overview survey of different types of rare diseases that have had new discoveries due to next-generation sequencing. Third, we discuss the obstacles and challenges that allow for clinical implementation, including returning of results, informed consent and privacy. Last, we discuss possible outlook as clinical genomics receives wider adoption, as third-generation sequencing is coming onto the horizon, and some needs in informatics and software to further advance the field.